MANAGEMENT OF QUANTITY OF TEACHING STAFF RATES AND ENROLLMENT PLAN OF EDUCATIONAL ORGANIZATION OF HIGHER EDUCATION - Andrew S. Zuev; Tatiana V. Lentyaeva (Высшее образование в России)
The article considers the problems of management of quantity of teaching staff rates and the enrollment plan of educational organization of higher education on the basis of the contingent of students, working curricula and the target figures of reception (TFR). The enrollment plan is supposed consisting of TFR on the places financed by means of the state budget, and enrollment plan for a contractual basis of training. The given problems are solved in common on the basis of application of the mathematical model offered by authors.